Abstracts of Philippine researches in social work, 1951-1976 - Ferrer, Susana Santos, 1938-
Author, title and subject indexes are provided to enhance the usefulness of the bibliography and thus facilitate the location of each entry. Numerals in these indexes refer to item numbers not to page numbers.
The arrangement of entries follows a chronological sequence to show the progress made in the field of social work and within the year alphabetically by authors. Each entry includes the name of the author, the title, year of completion, collation, the degree in parentheses, University or College to which thesis/dissertation was submitted, adopting the punctuation prescribed by the International Standard Bibliographic Description (ISBD) for Monographs, Chapter 6, except for published articles, followed by the location symbol. Immediately below the bibliographic description is the abstract of the material.
The research method employed in this study was the normative type of descriptive research wherein twenty-six (26) institutional/college/university libraries located in the Metropolitan Manila area were surveyed and their holdings on researches in the field checked through their catalogs and indexes. Likewise, several bibliographies and indexes were consulted to verify the existence of researches, theses and dissertations.
This compilation of abstracts of Philippine researches in social work for the period 1951-1976 (26 years) has been undertaken to preserve and document the knowledge contained in various theses and dissertations and published researches. This abstract bibliography of three hundred and sixty-two researches hopes to facilitate the efforts of professional social workers, the academic group, researchers, as well as students in identifying what has already been written in the field which are not readily accessible to them. Through this volume researchers are alerted of the existence of works completed in the various disciplines of and related to social work. Thus, duplication will be avoided and the researcher will be able to direct himself towards a more substantial, relevant and untouched field of studies.
Includes indexes
Mimeographed.
Thesis (M.L.S)--University of the Philippines, Diliman
Keywords: Social service--Research--Philippines--Bibliography.